2007
DOI: 10.1007/s00423-007-0251-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of interleukin-1 receptor antagonist (IL-1ra) in thyroid cancer patients

Abstract: The findings of our study indicate that IL-1ra may play an important role in the development of ATC and FTC. Future efforts should focus on the possible application of IL-1ra as a biomarker for the above-mentioned thyroid malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…For instance, the IL-1 antagonist, IL-1Ra has been shown to be overexpressed in multiple cancers, including multiple myeloma, leukemia, cervical, ovarian, colorectal, pancreatic and breast cancer, [53][54][55][56][57][58] but to be downregulated in others. 59 Similarly, high expression of the IL-1ra correlates with either better 54,56,[60][61][62][63] or worse cancer prognosis 62,64,65 This variability could stem from differential requirements of the two IL-1 cytokines in different cancers. Using KM plotter we have found that breast cancer patients expressing high levels of IL-1a had a better prognosis compared with patients expressing low levels of this cytokine, 48 consistent with a role of IL-1a as a negative regulator of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the IL-1 antagonist, IL-1Ra has been shown to be overexpressed in multiple cancers, including multiple myeloma, leukemia, cervical, ovarian, colorectal, pancreatic and breast cancer, [53][54][55][56][57][58] but to be downregulated in others. 59 Similarly, high expression of the IL-1ra correlates with either better 54,56,[60][61][62][63] or worse cancer prognosis 62,64,65 This variability could stem from differential requirements of the two IL-1 cytokines in different cancers. Using KM plotter we have found that breast cancer patients expressing high levels of IL-1a had a better prognosis compared with patients expressing low levels of this cytokine, 48 consistent with a role of IL-1a as a negative regulator of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noticed that IL1RA is an acute phase marker and high levels have previously been associated with aggressive disease and/or adverse prognosis in various malignancies, including T cell lymphoma [ 82 ], sarcoma [ 83 ], colorectal cancer [ 84 , 85 ], and thyroid cancer [ 86 ]. Our present study is the first to suggest that this is true also in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, increased levels of IL-1Ra were observed in numerous malignancies, including colorectal cancer (Iwagaki et al, 1997;Ito and Miki, 1999;Kaminska et al, 2000), multiple myeloma (Gherardi et al, 1996), ovarian cancer (Mustea et al, 2008), leukemia (Barak et al, 1998), cervical carcinoma (Fujiwaki et al, 2003), pancreatic cancer (Ebrahimi et al, 2004;Poch et al, 2007), uveal melanoma (Lee et al, 2012), prostate cancer (Parekh et al, 2007), breast cancer (Lv et al, 2011), and thyroid cancer (Niedźwiecki et al, 2008). It is interesting that elevated concentrations of IL-1Ra were associated either with greater (Iwagaki et al, 1997;Ito and Miki, 1999;Kaminska et al, 2000;Fujiwaki et al, 2003;Parekh et al, 2007;Niedźwiecki et al, 2008) or lesser (Gherardi et al, 1996;Parekh et al, 2007;Poch et al, 2007) disease severity.…”
Section: Il-1ra Restrains Il-1mentioning
confidence: 99%